CUSTOMS AND TRADITIONS OF TAJIKS OF THE FERGHANA VALLEY RELATED TO THE BIRTH OF CHILDREN AND WEDDING RITUALS (AS AN EXAMPLE OF TAJIKS KARATEGIN) (Scientific journal of the Fergana State University, 2024)
This article delves into the historical and cultural aspects of the migration of the Tajik people of Qarategin to the Fergana Valley over several centuries. It also examines their migration history and reasons, cultural practices, customs, and the order of their celebrations and rituals, as well as the process of their cultural adaptation with other ethnic groups in the valley, based on ethnological investigations and sources in academic literature. Furthermore, it analyzes, from an ethnological perspective, the unique customs and traditions of the Qarategin Tajiks related to childbirth and wedding ceremonies, the historical factors contributing to their formation, their goals and perceptions reflected in the execution of these customs, and the reasons for the contemporary changes in these traditions. Research within the scope of this study collected materials from the regions of Bobochek, Shamsiko‘l, Chodak, and Qizilqiyoq in the Fergana Valley where Tajik communities reside, mainly through observation, interviews, and questionnaire surveys. The scientific conclusions drawn from this research are based on the data obtained from these materials. The findings of this study underscore the cultural integration of Qarategin Tajiks, living in the Fergana Valley, with other communities over centuries, emphasizing their distinctive features and aspects that have persisted through time.